Normalisasi dan Pemulihan Masjid Nurul Yaqin Pasca-Banjir Bandang di Aceh Tamiang - Ariansyah, Jeri; Hanurisky, M. Dhani; Pratama, Muhammad Akbar; I'tisham, Abiyyu; Almuchty, Muhammad Aufathan (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
Flash floods in Aceh Tamiang Regency caused the Nurul Yaqin Mosque in Sapta Marga Village to be used as a temporary evacuation shelter, leading to severe post-disaster sanitation problems. The mosque was heavily contaminated by mud deposits and major impurities due to inadequate sanitation facilities, rendering it unsuitable for worship. This Community Service (PKM) program aims to restore the mosque’s function as a sacred place of worship and a center of community resilience. The method employed is the APKL approach (Actual, Problematic, Feasibility, and Appropriateness), implemented through outreach, education on fiqh thaharah (Islamic purification procedures), and technical cleaning using high-pressure water compressor technology. The results indicate that the mosque has been successfully cleaned and purified in accordance with Islamic law, making it fit for congregational worship again. The success indicators include the restoration of cleanliness and sanctity of the mosque, improved community understanding of purification procedures, and the reactivation of the mosque as a center for religious and social activities. Additionally, the program encourages community participation and creates economic empowerment opportunities for local youth through the use of cleaning technology to establish a sustainable vehicle washing business (doorsmeer). This program demonstrates that post-disaster mosque restoration not only addresses physical recovery but also strengthens social resilience and community economic independence.